AB0929 THE IMPACT OF KINESIOPHOBIA ON GAIT KINEMATICS IN PATIENTS WITH SPONDYLOARTHROPATHIES - Schweiger, Isabella; Koschinsky, J.; Elie-Tino, Godonou; Tascilar, Koray; Coppers, Birte; Kleyer, Arnd; Morf, Harriet; Simon, David; Bayat, Sara; Bohr, Daniela; Valor, L.; Raimondo, Maria Gabriella; et al. (Annals of the Rheumatic Diseases, 2024)
Background: In light of much needed functional assessments to monitor disease activity and functional status in spondyloarthritis (SpA), gait analysis is gaining interest. While it is generally known that the functional status and gait kinematics are closely related, it is unclear how fear of movement (kinesiophobia) affects gait kinematics in SpA patients. Objectives: To assess the influence of kinesiophobia on gait kinematics in patients with SpA and how sex mediates this relationship. Methods: A standardized 2-minute walk with self-selected walking speed was performed with 104 patients (psoriatic arthritis (PsA, CASPAR criteria) and ankylosing spondylitis (axSpa, ASAS criteria) (Internal Medicine 3 outpatient clinics Erlangen, Germany) in the hospital hallway. Spatio-temporal gait parameters (number of analyzed steps, cadence, gait velocity, double stance length and duration, swing left and right, stance left and right, temporal and spatial gait cycle variability) were recorded using the inertial sensor system RehaGait® (Hasomed, Magdeburg, Germany) and sagittal joint angles were computed and analyzed via MATLAB [1] (of the whole gait cycle the maximal and minimal flexion angle of left and right hip, knee, ankle). Patient characteristics and clinical assessments were retrieved from the patients record on the day of the gait analysis. Additionally, patients were asked to fill out the tampa scale of kinesiophobia (TSK) and an anamnestic questionnaire. Multivariate multiple linear regression was used to investigate the relationship between TSK score and kinematic gait parameters; mediation analysis was computed with sex as the control variable (potential mediator). Results: Patients characteristics of the 104 participants in this study are summarized in Table 1. Kinesiophobia affected the mediator sex (0.039; CI (0.005, 0.074), p=0.026) and the effect of kinesiophobia on gait kinematics differs between sexes. When controlling for the TSK score, male subjects took fewer steps and had a longer stance length. This may be due to them being taller (female: 166.6 cm, male: 179.9 cm; p<0.001). When controlling for sex, kinesiophobia is significantly associated with gait velocity (Coef: -0.009, p=0.003), double stance length (Coef: -0.005, p=0.031), double stance duration (Coef: 0.004, p=0.007), cadence (Coef: -0.39, p=0.006), swing phase left (Coef: -0.089, p=0.006) and the minimal left knee angle (Coef: -0.002, p=0.046). Conclusion: Patients with higher fear of movement scores by TSK walked slower, had a lower cadence, took smaller steps and had an increased extension of the left knee. While previous studies [2, 3] reported a decreased range of motion in axSpa patients compared to healthy subjects our results suggest that this can not only result from disease status itself, but that gait kinematics are associated with fear of movement. This is important to consider when gait analysis is used to assess the effect of interventions on functional status in SpA patient

AB0930 Towards Objective Measurement Of Spinal Mobility In Axial Spondyloarthritis – Benchmarking An Inertial Measurement Unit System With An Optical Measurement System - Blazek, V.; Loy, N.; Jukic, Elke; Coppers, Birte; Fleischmann, Martha Elisa; Hübner, Julian; Iqbal, M.; Heinrich, Simon; Scheiterer, Eduard; Leyendecker, Sigrid; Greenfield, Julia; Labinski, H.; et al. (Annals of the Rheumatic Diseases, 2024)

A novel Slide-seq based image processing software to identify gene expression at the single cell level - Götz, Theresa; Cong, X.; Rauber, Simon; Angeli, Mario Raphael; Lang, E. W.; Ramming, Alina; Schmidkonz, Christian (Journal of Pathology Informatics, 2024)
Analysis of gene expression at the single-cell level could help predict the effectiveness of therapies in the field of chronic inflammatory diseases such as arthritis. Here, we demonstrate an adopted approach for processing images from the Slide-seq method. Using a puck, which consists of about 50,000 DNA barcode beads, an RNA sequence of a cell is to be read. The pucks are repeatedly brought into contact with liquids and then recorded with a conventional epifluorescence microscope. The image analysis initially consists of stitching the partial images of a sequence recording, registering images from different sequences, and finally reading out the bases. The new method enables the use of an inexpensive epifluorescence microscope instead of a confocal microscope.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Cell segmentation; Deep neural networks; DNN complexity; Pruning; Slide-seq

Impact of the digital health application ViViRA on spinal mobility, physical function, quality of life and pain perception in spondyloarthritides patients: a randomized controlled trial - Palm von Alten Blaskowitz, Paloma Alexandra; Liphardt, Anna-Maria; Bouzas, Claudia; Coppers, Birte; Petit, Pascal; Vuillerme, Nicolas; Bundle, Vanessa; Rudolf, Sebastian; Knitza, Johannes; Raimondo, Maria Gabriella; Labinsky, Hannah; Hatscher, Lukas; et al. (Arthritis Research & Therapy, 2024)
Background: Spondyloarthritides (SpAs) are a group of common rheumatic diseases that often cause limited mobility and lower back pain. Physiotherapy is an integral part of treatment, but access to physiotherapy limits treatment success. Digital health applications (DHAs) enable home-based physiotherapy and could significantly improve access for SpAs patients. The aim is to investigate the clinical effects of the DHA ViViRA compared with those of standard physiotherapy. Methods: SpAs patients with chronic back pain were enrolled in a randomized controlled trial. The intervention group received ViViRA DHA, whereas the control group received standard physiotherapy. Pain (verbal rating scale, PAIN-Detect), quality of life (SF-36) and mobility (BASMI) were assessed at baseline and after 12 weeks as the primary outcomes. Results: Data from 59 participants (71.2% female, mean age 45.2 years) were analyzed. The intervention group showed a significant improvement in mobility (average BASMI score: baseline: 1.1 [range 0.7–1.5]; follow-up: 1.0 [range 0.5–1.4]; p = 0.05), whereas the control group showed a significant decrease in mobility (baseline: 1.5 [range 1.1–1.9]; follow-up: 1.8 [range 1.4–2.2]; p = 0.00). The intervention group demonstrated lower pain intensity (VRS pain level at week 3.5 ± 2.8) than did the control group (VRS pain level at week 4.5 ± 2) after 12 weeks. Conclusion: Our results highlight the efficacy of DHAs such as ViViRA in the treatment of lower back pain in SpAs patients. Compared with the current gold standard, physiotherapy, DHA use results in superior outcomes. However, further larger studies are needed to confirm these promising results. Trial registration: The study is registered in the German clinical trial registry (DRKS) under the following ID: DRKS00031254.
CRIS-Team Scopus Importer:2025-02-04
Keywords: DHA; Digital health application; E-Health; Mobility; Physical function; Psoriatic spondylitis; Spondyloarthritides; Spondyloarthropathy; ViViRA

POS0494 Fear Of Movement Affects Range Of Motion During Repeated Basmi Exercises Assessed By State-Of-The-Art Motion Capture Techniques - Loy, N.; Blazek, V.; Jukic, Elke; Fleischmann, Martha Elisa; Coppers, Birte; Hübner, Julian; Iqbal, M.; Heinrich, Simon; Scheiterer, Eduard; Leyendecker, Sigrid; Greenfield, Julia; Labinski, H.; et al. (Annals of the Rheumatic Diseases, 2024)
Background: Quantification of spinal mobility in chronic axial spondyloarthritis (axSpA) is an important component of disease assessment and is currently assessed using the clinical Bath Ankylosing Spondylitis Metrology Index (BASMI). Functional movement-based outcome measures are dependent on a number of secondary factors and, in particular, the impact of fear of movement on BASMI performance in axSpA patients is currently unknown. Objectives: To investigate the association of range of motion (RoM) for repeated BASMI exercises detected by inertial measurement units (IMU) and optical-measurement system (OMS) motion capture with fear of movement by Tampa Scale of Kinesophobia 17 (TSK) [1)] in axSpA patients. Methods: AxSpa patients (Internal Medicine 3, Universitätsklinikum Erlangen) and healthy controls (HC) were asked to fill out the TSK and BASMI was performed and scored for three repetitions for each task by a trained physician. The BASMI tasks were performed a second time on the same day as the clinical assessment using OMS. Fifty-four retro-reflective markers and 16 IMU devices (myoMOTION by Noraxon, Scottsdale, USA) were placed on defined anatomic sites (Figure 1) and marker motion was detected with 11 infrared cameras (Oqus 7+, Qualisys, Göteborg, Sweden). BASMI values for each task were analysed in distance (cm) or degree of rotation. A correlation matrix was used to assess the relationship between TSK score and BASMI task 5 (lateral neck flexion in degrees) values from the OMS and IMU data, using the Pearson product moment correlation. Exact BASMI values in degrees and clinical BASMI value per group are reported as means ± standard deviation (SD). Results: Fifty participants were included in the study (30 axSpa patients (12/16 male/female, age: 41.9 (SD 12.3), C-reactive protein: 5.2 (13.8) mg/l and visual analog scale (VAS) global: 4.1 (SD 2.7)) and 20 HC (9/11 male/female, age: 28.4 (SD 3.7) and VAS global 0.1 (SD 0.29)). Measurements from two patients were excluded due to failed IMU und OMS data post-processing, resulting in 28 patients for this analysis. Correlation results between the exact BASMI-5 scores (degree of rotation) for each of the three repetitions and the TSK scores are presented in Table 1. AxSpA patients showed a positive, but not significant (p>0.05) correlation between OMS and TSK score, and a positive, significant (p<0.05) correlation between IMU and TSK score data. The correlation remained stable over the three repetitions. For the IMU data, significant correlations with the tendency of higher values over each of the three repetitions for both groups were observed. In contrast, the HC values showed a negative correlation for both the OMS and IMU values with the TSK score. An increase over the three repetitions in the negative correlation can be seen for both measurement systems. Conclusion: Our results suggest positive relationship between fear of movement and cervical movement restriction in axSpa patients. In addition, axSpA patients tended to achieve higher levels of mobility on repetition of exercise than at baseline. This influence of fear of movement on functional outcomes is especially visible in the IMU data for the axSpa patients. In contrast, the relationship between fear of movement and cervical movement tends to be negative for HC, suggesting that in healthy subjects fear of movement assessed over the TSK does not impact the objectively measured cervical mobility. Further analysis will include a wider range of BASMI tasks to identify movements that might be particularly prone to impairments due to fear of movemen